Effectiveness and satisfaction of home-based external bleaching - Basudan, Thuraya Abdulrahim; Alshehri, Dhafer Mohammed; Abu Msmar, Omar Abdulaziz; Hakami, Muath Ali; Alafra, Saeed Hadi; Alsanah, Abdullah Saeed; Alshahrani, Nasser Mohammed; Alqahtani, Faris Ali (International Journal Of Community Medicine And Public Health, 2022)
Hydrogen peroxide is the main ingredient in bleaching products (BP), and based on the settings of the reaction, can produce (per-)hydroxyl anions, superoxide anions, and other radicals. The radical-related oxidative mechanism can trigger the breakage of molecular bonds in enameller and dentinal stains, while the exact process is not entirely grasped. Products as a consequence look less colorful. The amount of the active bleaching component, the likelihood of BP interaction with discolorations, and the contact duration all affect the effectiveness of the bleaching treatment. Effectiveness also depends on a number of variables, including the individual's age, the type of staining, and the number of bleaching treatments. A significant number of local adverse effects have been recorded with over-the-counter items due to poorly fitted tray, adjuvants such as binders, preservatives, and flavors as well as a low pH, coexisting gingivitis, abrasion, and erosion. In cases of the coupled utilization of tobacco and excessive alcohol intake because tobacco users demonstrate lower levels of hypersensitivity to the BP and may be heavily influenced by the positive cosmetic effects, they must particularly be counseled against getting bleaching done as the combination has been found to pose elevated oral carcinoma risk. Overall, current literature has found a positive relation between procedure efficacy and patient satisfaction.